Dampak Hibah FOLU Norwegia terhadap Pertumbuhan Ekonomi Hijau Indonesia: Analisis Input-Output - Galuh Sukarsa; Muhammad Heru Akhmadi (Yayasan Ekologi Masyarakat dan Sains, 2026)
Multinational financing facilities to improve environmental quality had been implemented by Indonesia at the fourth quarter of 2022, as Norway’s grant about USD 56 under the Forestry and Other Land Use (FOLU) Net Sink 2030 program. This study aims to assess the effectiveness and impact of the Norwegian grant on the development of Indonesia’s green economy using Indonesia’s 52-sector Input-Output analysis 2016 that already updated to 2025, interviews and documentation. This research finds that Norway’s grant was allocated under a Result-Based Contribution (RBC) scheme, achieved an effectiveness rate of 52% in 2023. It also boosted economic growth through increased output (Rp735,39 billion) and gross value added (Rp607,80 billion), enhanced by downstream forest product industries. Nonetheless, optimization gaps remain, particularly in governance quality, stakeholder synergy, and community-based downstream forestry initiatives.